Pengaruh Kualitas Produk dan Promosi Penjualan Terhadap Keputusan Pembelian pada Toko Mitra Parfum Telukjambe Karawang - Ica Lupita Yoeanda; Savitri, Citra; Wike Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this research, the author aims to determine and analyze the influence of product quality and sales promotions on purchasing decisions at Telukjambe Karawang perfume partner stores. This research is quantitative descriptive. The data in this study was collected through a questionnaire distribution technique to 138 respondents who were consumers of perfume partner shops. The data analysis method uses path analysis. The test results show that product quality has a significant partial influence on purchasing decisions. Sales promotions have a partial influence on purchasing decisions, product quality and sales promotions simultaneously have an influence on purchasing decisions. Therefore, it can be concluded that, the higher the quality of the product, the greater the purchasing decision, and the better and more attractive the promotions are, the higher the purchasing decision at the Mitra Perfume Store.